Phytoestrogens in postmenopausal indications: A theoretical perspective - Sunita, P.; Pattanayak, S. P. (Pharmacognosy Reviews)
This review discusses plant-derived compounds with estrogenic activity. The authors rightly emphasize the need for the intake of foods containing phytoestrogens in view of their positive effects on postmenopausal indications. This is particularly significant in the light of the current wave of enthusiasm for vegetarian food, in general, and phytoestrogens, in particular. Phytoestrogens are plant-derived hormone-like diphenolic compounds of dietary origin. These compounds are weakly estrogenic and could play a role in the prevention of other estrogen-related conditions, namely, cardiovascular diseases, menopausal symptoms, postmenopausal osteoporosis, neuroprotective effects, and hormone-dependent cancers (breast and endometrium cancer).
Keywords: Menopause; menopausal indications; phytoestrogen